Tree species diversity and forest stand dynamics in a tropical rainforest in Southern Nigeria - Sanwo, S.K.; Ige, P.O.; Sosanya, O.S.; Ogunlaye, O.G. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Twenty temporary sample plots were laid in Onigambari Forest Reserve, one of the major rainforest reserves in Nigeria (latitude 7º 25’ and 7º 55’N and longitude 3º 53’ and 3º 9’E) in an attempt to study the tree species diversity and stand structure. The sample plots were laid using systematic line transects. In each sample plot, all trees with a diameter at breath height (dbh) above 10 cm were identified by species and measured. The results show that the mean tree basal area obtained ranged from 0.5824 m2/ha to 0.8116 m2/ha. The mean number of stems and species per hectare on the different transects varied from 85 – 89 and 36 – 40, respectively. The differences between the transect lines were not statistically significant indicating a uniform nature of distribution of species and individuals trees in the forest. A total of 335 stems comprising 63 species and belonging to 25 families were encountered. Family Ebenaceae had the highest representation (17.31%) and Diospyros dendo (Ebony) was the most common member of this plant family.